2003
DOI: 10.1126/science.1079731
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Multispecificity Mediated by Conformational Diversity

Abstract: A single antibody was shown to adopt different binding-site conformations and thereby bind unrelated antigens. Analysis by both x-ray crystallography and pre-steady-state kinetics revealed an equilibrium between different preexisting isomers, one of which possessed a promiscuous, low-affinity binding site for aromatic ligands, including the immunizing hapten. A subsequent induced-fit isomerization led to high-affinity complexes with a deep and narrow binding site. A protein antigen identified by repertoire sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
603
3
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 670 publications
(631 citation statements)
references
References 32 publications
22
603
3
3
Order By: Relevance
“…However, recent crystallographic and thermodynamic analyses of both germline and mature Ab-Ag complexes have suggested that the Ab repertoire can be further enhanced at the tertiary structural level (7,14,18,19,34,35). The present study provides an elegant correlation of CDR conformational versatility in a germline Ab with its multispecificity.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, recent crystallographic and thermodynamic analyses of both germline and mature Ab-Ag complexes have suggested that the Ab repertoire can be further enhanced at the tertiary structural level (7,14,18,19,34,35). The present study provides an elegant correlation of CDR conformational versatility in a germline Ab with its multispecificity.…”
Section: Discussionmentioning
confidence: 69%
“…Six structures of the germline mAb BBE6.12H3, in different chemical environments, quantitatively define the conformational repertoire of the CDRs, providing a rich data set for examining paratope topologies, although thermodynamic and computational studies have provided interesting clues regarding the generation of diversity in primary Ab response (5,19,33,34). Similarly, crystallographic and kinetic analyses of mature Abs SPE7 and NQ22/61.1, respectively, have also suggested conformational isomerism (7,19). Our data consisting of six BBE6.12H3 Fab structures-two Ag free and four Ag bound-provided a rich source of information reflecting correlation of paratope conformational flexibility and polyreactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations imply evolutionary acquisition of new protein functions (Aharoni et al, 2005), which appears to have been the evolutionary progression of the pgf proteins among marine and terrestrial vertebrates (Kitagawa et al, 1993). James et al (2003) have suggested that conformational diversity, i.e., one sequence adopting multiple structures and functions, as in the conserved sequences among pgf proteins, can increase the numbers of potential antibody targets, thereby enhancing the likelihood of developing cross-reactivity, which can result in autoimmunity (Cohn, 2005). Our present results may also be consistent with that proposition.…”
Section: Mab Recognition Of Neuronsmentioning
confidence: 98%
“…In particular, the importance of antibody multispecificity is obvious in the humoral immune system [21], where a limited set of antibodies must bind a virtually unlimited range of antigens. However, the proper examples of such multispecificity are confined to the few hapten-binding antibodies [22].…”
Section: Introductionmentioning
confidence: 99%